The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1113/jphysiol.2003.056598
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes, cytokines, growth factors and hormones in human skeletal muscle and blood after uphill or downhill running

Abstract: Muscular adaptation to physical exercise has previously been described as a repair process following tissue damage. Recently, evidence has been published to question this hypothesis. The purpose of this study was to investigate inflammatory processes in human skeletal muscle and epimysium after acute physical exercise with large eccentric components. Three groups of subjects (n = 19) performed 45 min treadmill running at either 4 deg (n = 5) or 8 deg (n = 9) downhill or 4 deg uphill (n = 5) and one group serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
193
6
17

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(246 citation statements)
references
References 46 publications
30
193
6
17
Order By: Relevance
“…Many investigators have reported no effect of exercise on IL-10 secretion (15,31), while others have observed increased plasma IL-10 levels following exercise (17,32). Similar to the present study, Brenner et al (22) have described a reduction in plasma IL-10 levels following "all-out" cycling (5 min, 90% of VO 2max ), supporting the concept that the pattern and magnitude of the IL-10 response vary with exercise intensity and duration.…”
Section: Discussionsupporting
confidence: 79%
“…Many investigators have reported no effect of exercise on IL-10 secretion (15,31), while others have observed increased plasma IL-10 levels following exercise (17,32). Similar to the present study, Brenner et al (22) have described a reduction in plasma IL-10 levels following "all-out" cycling (5 min, 90% of VO 2max ), supporting the concept that the pattern and magnitude of the IL-10 response vary with exercise intensity and duration.…”
Section: Discussionsupporting
confidence: 79%
“…quadriceps) move through the swing-lengthening phase of the running motion. If the primary force is only applied at the end of the action, it is possible that the primary stress is on collagen and tendon structures outside the muscle fibre; 10 this would be supported by findings of Malm and colleagues, 11,12 who D. Gastrocnemius suggest that after downhill running, inflammatory factors are present in muscle epimysium and that the focal injury does not exist in muscle.…”
Section: Neutrophil and Monocyte Countsupporting
confidence: 50%
“…Previous studies, using downhill running, have generally taken blood samples starting at 24 h after the exercise bout. 2,3,12 We believe this is the first study to demonstrate that significant differences occur as early as 3 h after the downhill run.…”
Section: Creatine Kinasementioning
confidence: 98%
See 1 more Smart Citation
“…However, during excessive prolonged exercise (>3h), the concentration of circulating NK cells may return to the pre-exercise level, or even become lower 62 . It is hypothesized that this decrease is due to the migration of these cells to sites of muscular injury 63 . Some studies demonstrate that the two subgroups, CD56bright and CD56dim, increase during exercise; however, there is a differential mobilization between them.…”
Section: Nk Cellsmentioning
confidence: 99%